A review on ethno-medicinal plants used in west Kalimantan - Dodi Iskandar; Nashi Widodo; Warsito Warsito; Masruri Masruri; Rollando Rollando (International Journal of Agricultural Sciences, 2022)
The purpose of the current study is to review ethno-medicinal plant used by natives in West Kalimantan Province in last five years. The methods used is gathering earlier publications in journals completed with pharmacological evidence of local medicinal plants. The present review result reported that 346 specieses belonging to 95 families have been utilized in West Kalimantan Province. Zingiberceae has the top number of plant of families (25) followed by Rubiaceae (17), Fabaceae (16), Asteraceae (14), Euphorbiaceae (13), Poaceae (13), Verbenaceae (13), Liliaceae (10), other families (<10).  The tabulated plant species in this study are frequently used as herbal medicine for the treatment of miscellaneous deseases and the medication safety of local people. Parts of plant used as herbal medicine are leaves (46.1%) followed roots (15.7%), fruits (9.5%), rhizomes (6.7%), all parts (5.9%), stems (5.4%), seeds (2.3%), saps (1.3%), pericarps (1.0%), flowers (0.8%), shoots (0.8%), stalks (0.8%), tubers (0.8%), and twigs (0.3%). The majorities of used methods for traditional medicine are decoction and infusion. The information of this current review includes local names, species, families, used parts, and medical uses. All the medicinal plants reported in this study have been used by West Kalimantan people for the treatment of various deseases